The Analysis of the Effect of Population Growth on Changes in Built-Up Area Density in Kupang City in 2020 and 2024 Using the Normalized Difference Built-Up Index (NDBI) Method - Lastawan, Indah; Muhammad Husain, Hasan; Rahmawati, Arfita (Jurnal Geografi : Media Informasi Pengembangan dan Profesi Kegeografian, 2025)
The dynamics of urban development in Kupang City are strongly influenced by population growth and the increasing need for urban space. This study aims to analyze the relationship between population growth and changes in built-up area density in 2020 and 2024 using the Normalized Difference Built-Up Index (NDBI) from Landsat 8 OLI/TIRS Level-2 imagery. This study uses a spatial quantitative approach with the integration of remote sensing techniques, geographic information systems (GIS), and statistical analysis. Population data were obtained from the Central Statistics Agency (BPS) of Kupang City, while spatial data were from the USGS with a path/row of 110/070 and a cloud-free acquisition rate of <10%. Image processing includes atmospheric correction (LaSRC), cloud masking, cropping of administrative boundaries, and calculation of the NDBI index. NDBI values are classified into three categories: low ( −0.2–0.0), medium (0.01–0.2), and high (>0.2) based on the reference of Dewi et al. (2023). Field validation was conducted at 20 sample points with an accuracy of 87%. The results show a significant increase in built-up areas in Maulafa, Alak, and Oebobo, which aligns with the population growth trend in these sub-districts. Pearson's correlation (r = 0.418) indicates a positive relationship between population growth and built-up density. This finding confirms the relevance of the NDBI as a tool for monitoring urbanization in medium-sized cities in Eastern Indonesia